Neighboring Pd single atoms surpass isolated single atoms for selective hydrodehalogenation catalysis - Chiheng Chu; Dahong Huang; Srishti Gupta; Seunghyun Weon; Junfeng Niu; Eli Stavitski; Christopher Muhich; Jae-Hong Kim (Nature Communications, 2021)
Single atom catalysts have exhibited high selectivity for hydrogenation, yet improved selectively is often accompanied by loss of activity. Here the authors report that synergistic interactions of neighboring Pd single atoms lead to both high activity and selectivity for hydrodehalogenation catalysis.